Impact Analysis of Transformer Extension and Network Maneuvering Strategy on Tulungagung Substations - RIVALDO SETYA PAMUNGKAS; CANDRA FEBRI NUGRAHA (Institut Teknologi Nasional, Bandung, 2026)
Increasing electricity demand in Tulungagung has caused transformers at Substation 1 and 2 to reach critical loading. To address this, PT PLN (Persero) UP3 Kediri added a 60 MVA transformer at the New Tulungagung Substation with load redistribution. This study analyzes the impact of the new transformer on transformer loading, power losses, and voltage profile, and identifies the most efficient network maneuver scheme during maintenance. Simulationsusing DIgSILENT PowerFactory were based on Tulungagung distribution data. results show reduced loading to 62.8% and 70.5%, improved minimum voltage from 0.91 p.u. to 0.93 p.u., and loss reduction from 2.84 MW to 2.71 MW (4.6%). Among three maneuver schemes, the third achieved the best performance with 0.94 p.u. minimum voltage and 3.90 MW losses. The new transformer significantly enhances system efficiency and reliability.